Salivary IgA is not a reliable indicator of upper respiratory infection in collegiate female soccer athletes - Vardiman, J. P.; Riggs, C. E.; Galloway, D. L.; Waxman, M. B.; Touchberry, C. D.; Gallagher, P. M. (The Journal of Strength and Conditioning Research, 2011)
It has been shown that mucosal immunity measures such as salivary immunoglobulin A (s-IgA) can be affected by sport activities and has resulted in an increased susceptibility to infection. However, there is limited research that has evaluated the change in s-IgA throughout a full sport training season. The purpose of the study was to evaluate the change in s-IgA levels and incidence of upper respiratory infection in the National Collegiate Athletic Association Division I level female soccer athletes compared to age matched controls over an entire sport training season. Saliva samples were collected from 12 randomly selected female collegiate soccer athletes and 8 age-matched controls. Samples were collected bimonthly from the athletes' pre-and post-sport training sessions and pre- and post-90-minute sedentary period for the controls. Analysis showed there was a significant (p < 0.05) group × time interaction in total protein (TP) for collections 1 and 4 and a significant (p < 0.05) group × time interaction in s-IgA/TP for collections 2 and 3. There was no significant difference (p > 0.05) between athletes and controls for s-IgA or total symptom days (TSDs). Furthermore, there was no significant correlation between absolute s-IgA and TSDs or s-IgA/TP and TSDs throughout the sport training season. The large range of measurable levels for s-IgA at the different time points for athletes and controls and the lack of relationship between s-IgA levels and TSDs indicate that s-IgA is not an appropriate measure to determine an athlete's susceptibility to during a training season.